A study on optical limiting properties of Eosin-Y and Eriochrome Black-T dye-doped poly (vinyl alcohol) composite film. Issue 4 (19th May 2019) - Manikandan, K. M.; Yelilarasi, A.; Senthamaraikannan, P.; Saravanakumar, S. S.; Khan, Anish; Asiri, Abdullah M.
Abstract: A poly (vinyl alcohol) PVA/Eriochrome Black-T (EBT) dye, and PVA/Eosin-Y (EY) dye composite film was prepared using a solution casting process. The dye-doped composite polymer films were characterized by UV–vis spectroscopy. An optical band gap ( E g ) of pure PVA reduced from 4.22 eV to 2.80 eV for PVA/EBT film and 2.14 eV for PVA/EY film respectively. This result indicates the occurrence of inter-molecular hydrogen bonding between the –OH functional group in PVA chains and sulfonate (EBT) and carboxyl group (EY) in dye molecules, respectively. Moreover, the experimental result of PVA/EBT and PVA/EY composite film showed the excellent properties of a large scale cut-off filter in the ultraviolet and visible range region.